Impact of individual social deprivation on environmental risk perception by French pregnant women. (30th September 2020) - Sauvant-Rochat, M P; Bernard, L; Pelissier, M; Marie, C; Lémery, D; Vendittelli, F
Abstract: Background: Individual social deprivation (ISD) can have significant impact on the life conditions. However, few studies explored the impact of ISD on the preventive behaviors adopted by pregnant women (PW) in relation to exposure of chemicals. AIM: This study aims to describe the link between ISD and the perception of chemical and environmental risks. Methods: A cross-sectional survey was performed among PW present in maternity hospitals in Auvergne (France). Face-to-face interviews with a standardized questionnaire were used to collect anonymously the data (socio-demographic characteristics, smoking behaviors, perception of environmental risks (PER Score based on Likert scale ranking from 0 to 10), individual social deprivation (by EPICES score)). Statistical analysis (univariate analysis - logistic regression) was performed with Modalisa® 8.0 (Kynos, Paris). Results: 300 PW (29±5 years old) were included. The majority of PW reported being aware of the risks associated with chemicals. The PER Score is estimated at 6.3±1.8. It was significantly associated with parity and trimester of pregnancy, and inversely linked to age of PW. The EPICES Score was 19.9 ±17.8 (rank: 0-85). With a precariousness threshold of 30, only a quarter of the PW were in a precarious situation. The EPICES Score was inversely related to age, smoking behaviors, and environmental risks perception. The criterion of choice of everyday products was linked to the EPICES score. 'Organic products' were mainly used by PW with EPICES Score < 30 (not precarious). Conclusions: The weight of social determinisms on environmental sensitivity highlights the need for targeted prevention. The role of health professionals in prevention and environmental health promotion is essential, especially to detect women of low socioeconomic status who may not be sensitive to media messages and prevention campaigns disseminated by health authorities. Key messages: Perinatal health professionals must have a major role in environmental health promotion, especially for pregnant women with individual social deprivation. Perception of chemicals and environmental risks was inversely linked to the individual social deprivation (EPICES score) in this French PW population.